Synthesis and Performance of Deca- Dodecasil 3 Rhombohedral (DDR)-Type Zeolite Membrane In CO2 Separation– A Review - Mubashir, Muhammad; Fong, Yeong Yin; Keong, Lau Kok; Bin Sharrif, Mohd. Azmi (ASEAN Journal of Chemical Engineering, 2014)
CO2 capture technologies including absorption, adsorption, and cryogenic distillation are reported. Conventional technologies for CO2 separation from natural gas have several disadvantages including high cost, high maintenance, occupy more space and consume high energy. Thus, membrane technology is introduced to separate CO2 due to their several advantages over conventional separation techniques. Inorganic membranes exhibit high thermal stability, chemical stability, permeability and selectivity for CO2 and CH4 separation as compared to other type of membranes. Zeolite membranes are potential for CO2 separation due to their characteristics such as, well define the pore structure and molecular sieving property. Among the zeolite membranes, DDR membranes exhibit highest selectivity for CO2 and CH4 separation. DDR membranes are synthesized by conventional hydrothermal and secondary growth methods. These methods required very long synthesis duration (25 days) due to extremely low nucleation and crystal growth rate of DDR zeolite. In this review, synthesis and performance of DDR membrane in CO2 separation from CH4 reported by various researchers are discussed. Challenges and upcoming guidelines related to the synthesis DDR membrane and performance of DDR membrane also included.